Anxiety Of Clare In Constance Briscoe's Ugly Novel (2006): A Psychoanalytic Approach - Hardanty, Cahyaningrum (2012)
The problem of the study is to reveal how major character reflects her anxiety. The objectives of the study is to analyze the novel based on its structural analysis and based on the psychoanalytic analysis. The study belongs to a qualitative study. In this method, the researcher uses two data sources namely primary and secondary data. The primary data source and object of study are the Ugly novel itself, meanwhile the secondary is any reference related the study. The technique of data analysis in this study is descriptive to make an interpretation of the text and content analysis using deductive and inductive method. The results of the study show the following conclusions. Firstly, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, theme and style related to each other and form a solid unity. Secondly, based on the psychoanalytic analysis, the writer concludes that the problems faced by the major character is anxiety due to bad treatment because she has an ugly face. It happens when there is conflict between Id, Ego and Superego and it brings her into anxiety.